Social Control And Legal Reform: A Study Of Minimum Marriage Age From The Perspective Of Islamic Law And Plural Legal Systems - Munawwir khaliq; Ahmad Muhasim; Arino Bemi Sado; Azman Ab. Rahman (Institut Agama Islam Negeri Kendari, 2026)
Non-Indexed Publication